2011
DOI: 10.1080/09658416.2011.570347
|View full text |Cite
|
Sign up to set email alerts
|

What makes pronunciation teaching work? Testing for the effect of two variables: socially constructed metalanguage and critical listening

Abstract: While there is growing evidence that pronunciation teaching can work, there is a need to establish what it is that makes it work. The study reported here tested for the effect of two particular factors: socially constructed metalanguage (SCM) and critical listening (CL). SCM is a term proposed for metalanguage developed by students working together with the teacher using already understood first language (L1) concepts to help in the formation of target language phonological concepts. CL is based on listening a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 22 publications
4
50
0
2
Order By: Relevance
“…aLVEs & MaGRO, 2011;CEBRIaN & CaRLET 2014;COuPER, 2011;RaMÍREz VERDuGO, 2006;RaTO, 2013;saITO, 2015;sILVEIRa, 2004;WREMBEL, 2005). as brought up by silveira and alves (2009), the instructor can have the facilitating role in helping learners to notice details of L2 speech which otherwise may be left unnoticed.…”
Section: Discussionmentioning
confidence: 99%
“…aLVEs & MaGRO, 2011;CEBRIaN & CaRLET 2014;COuPER, 2011;RaMÍREz VERDuGO, 2006;RaTO, 2013;saITO, 2015;sILVEIRa, 2004;WREMBEL, 2005). as brought up by silveira and alves (2009), the instructor can have the facilitating role in helping learners to notice details of L2 speech which otherwise may be left unnoticed.…”
Section: Discussionmentioning
confidence: 99%
“…After a 12‐week course, while both groups improved in terms of production of individual sentences, only the suprasegmental group showed progress in extemporaneous speaking. An example of research targeting language awareness in pronunciation comes from Couper (), who showed that pairing intensive listening practice with an approach allowing the instructor and the learners to develop a mutually agreed–upon set of metalinguistic descriptors for discussing pronunciation resulted in the best performance, compared to other approaches, in both perception and production. Both these lines of research have demonstrated that attention to pronunciation through explicit instruction is beneficial (as shown by Derwing et al, ), especially when learners are made aware of how L2 pronunciation works, for example, through metalanguage (as suggested by Couper, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is especially justified as previous research indicates that consciousness-raising activities, such as explicit teaching, for instance, are extremely beneficial for L2 speech development (e.g. ALVES; MAGRO, 2011;CEBRIAN;CARLET 2014;COUPER, 2011;RATO, 2013;SAITO;WU, 2014).…”
Section: Stress Placement Resultsmentioning
confidence: 99%